Human Capital dan Keunggulan Bersaing Ritel Minimarket: Strategi Sebagai Pemedias - Ardianus Laurens Paulus (Management Insight: Jurnal Ilmiah Manajemen, 2017)
This research aims to examine the influences of human capital toward competitive advantage mediating by strategy. This research employs quantitative approach using survey method. Data collection was conducted at 42 minimarket managers located in Madiun City, East Java, Indonesia. The data were analyzed using measurement model of structural equation modeling supported by Smart PLS 3.0 software. The results of the research find out that human capital has significant and positive influences towards strategy and competitive advantage. In addition, strategy has significant and positive influences toward competitive advantage. Whereas, strategy has partially mediated the influence of human capital toward competitive advantage.